Development of a non-destructive method to measure football facemask stiffness - Bina, A. J.; Batt, G. S.; DesJardins, J. D. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2019)
Despite heightened awareness of the need for more protective headgear in American football, facemask performance as an individual component of the helmet system has been overlooked. Current methods used to evaluate facemasks are ineffective in separating facemask performance from the performance of the full-helmet system. This article evaluates the use of a non-destructive, quasi-static loading method to measure the structural stiffness of 11 football facemask designs that represent various geometries and materials. The test method determined quantifiable differences in facemask stiffness, while limiting permanent facemask deformation to less than 3.175 mm. The reliability of the structural stiffness measurement process was assessed through a test-retest analysis of three facemask styles. The coefficient of variation for each style of facemask was between 1.1%-3.3%. This novel facemask stiffness test can be used for the non-destructive evaluation of facemasks by reconditioners, as well as facemask manufacturers to differentiate the potential impact performance of novel facemask designs.